Recovery from Multiple APAs Delays Gait Initiation in Parkinson’s Disease - Cohen, Rajal G.; Nutt, John G.; Horak, Fay B. (Frontiers in Human Neuroscience, 2017)
Background. Freezing of gait in Parkinson’s disease (PD) has been linked with deficits in inhibitory control, but causal mechanisms are not established. Freezing at gait initiation (start hesitation) is often accompanied by multiple anticipatory postural adjustments (APAs). If inhibition deficits contribute to freezing by interfering with ability to inhibit initial weight shifts in the wrong direction, then PD subjects should experience more episodes of multiple APAs than healthy controls do. If inhibition deficits contribute to freezing by interfering with ability to release a previously inhibited step following multiple APAs, then step onset following multiple APAs should be delayed more in people with PD than in healthy controls. Methods. Older adults with PD and healthy control (HC) subjects rapidly initiated stepping in response to a light cue in blocks of simple (SRT) and choice (CRT) conditions. We recorded kinematics and ground reaction forces, and we administered the Stroop task to assess inhibitory control. Results. Multiple APAs were more common in CRT than SRT conditions but were equally common in HC and PD subjects. Step onsets were delayed in PD subjects in both conditions and further delayed in trials with multiple APAs, especially in PD subjects with self-reported freezing. Stroop scores correlated with prevalence of multiple APAs and step onset latency; prevalence of multiple APAs did not correlate with step onset latency. Conclusions. Start hesitation is not caused by multiple APAs per se, but may be associated with difficulty recovering from multiple APAs, due to difficulty releasing a previously inhibited step.